Approaches to improve the utilization of food-feed crops - Seré Rabé, Carlos (Elsevier, 2003)
This special issue of Field Crops Research includes a series of papers presented at the International Workshop “Approaches to improve the utilization of food-feed crops” held at the International Livestock Research Institute (ILRI) in Addis Ababa, Ethiopia, from 29 to 31 January 2002. The workshop was organized jointly by CGIAR Systems-wide Livestock Programme, based at the International Livestock Research Institute (ILRI), and the International Crop Research Institute for the Semi-Arid Tropics (ICRISAT) with financial support from the Department for International Development of the United Kingdom.